Cognitive Reflection and the Diligent Worker: An Experimental Study of Millennials - Corgnet, Brice (PLoS One, 2015)
Recent studies have shown that despite crucially needing the creative talent of millennials (people born after 1980) organizations have been reluctant to hire young workers because of their supposed lack of diligence. We propose to help resolve this dilemma by studying the determinants of task performance and shirking behaviors of millennials in a laboratory work environment. We find that cognitive ability is a good predictor of task performance in line with previous literature. In contrast with previous research, personality traits do not consistently predict either task performance or shirking behaviors. Shirking behaviors, as measured by the time participants spent browsing the internet for non-work purposes (Cyberloafing), were only explained by the performance on the Cognitive Reflection Test (CRT). This finding echoes recent research in cognitive psychology according to which conventional measures of cognitive ability only assess a narrow concept of rational thinking (the algorithmic mind) that fails to capture individuals’ capacity to reflect and control their impulses. Our findings suggest that hiring diligent millennials relies on the use of novel cognitive measures such as CRT in lieu of standard personality and intelligence tests.